2014
DOI: 10.1088/0953-8984/26/9/093001
|View full text |Cite
|
Sign up to set email alerts
|

Controlling magnetism on metal surfaces with non-magnetic means: electric fields and surface charging

Abstract: We review the state of the art of surface magnetic property control with non-magnetic means, concentrating on metallic surfaces and techniques such as charge-doping or external electric field (EEF) application. Magneto-electric coupling via EEF-based charge manipulation is discussed as a way to tailor single adatom spins, exchange interaction between adsorbates or anisotropies of layered systems. The mechanisms of paramagnetic and spin-dependent electric field screening and the effect thereof on surface magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 196 publications
(343 reference statements)
0
51
0
Order By: Relevance
“…Even the simple effect of electrostatic screening in a metal is intrinsically quantum mechanical, as it is apparent from the spin-dependent screening in F, 31,32 shown in Fig. 2 for a Co slab.…”
mentioning
confidence: 99%
“…Even the simple effect of electrostatic screening in a metal is intrinsically quantum mechanical, as it is apparent from the spin-dependent screening in F, 31,32 shown in Fig. 2 for a Co slab.…”
mentioning
confidence: 99%
“…Whereas, a reduced variation of the spatial charge is also observed underneath the surface. Such charge re- distribution can even be spin-dependent which can alter the magnetic order 13,15 . Meanwhile, the exchange interaction across the coupling medium in Fe/Cu N /Fe trilayer, supported on a Pt(001) substrate, determines the magnetic state to be either ferromagnetic (FM) or antiferromagnetic (AF).…”
Section: Switching Interlayer Exchange Coupling With Surface Chamentioning
confidence: 99%
“…Recently a more efficient method has been revealed, on the basis of magnetoelectric coupling, for tuning the spin alignment in a ferromagnet (FM) by both Density Functional theory [12][13][14][15][16] and experimental studies 1,17,18 . For instance, the anisotropy properties of 2D ferromagnet could be tuned either by varying its intrinsic charge carriers 12,15 or the oxidation state by electric means 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, looking for materials with large MA is of importance for spintronics applications [7] and data storage [17]. Recent studies have shown that the magnetic moment and the MA in monolayer and bulk materials can be induced, modified, and tuned using an electric field (E field) [18][19][20][21], surface charging [22][23][24][25], applying biaxial strain [26][27][28][29], doping transition metal and other atoms [30,31], and dimers [32,33].…”
Section: Introductionmentioning
confidence: 99%